(untitled) (Research, Society and Development, 2021)
The solar desalinator is a viable and low-cost technology for using energy from the sun. In addition, it is resistant to high temperatures, obtaining reasonable amounts of water. The objective of this work is to present the influence of climatic, operational and design parameters on the thermal performance and productivity of the solar desalinator. To satisfy this objective, a sequential description of the factors that interfere with the solar distillation process was chosen. The results indicated that solar desalination is affected by the evaporation area, water depth and the desalination cover angle. The isolation of the desalination system positively affected productivity, because it increased the heating capacity and the evaporative effects within the desalinator. It was also found that the performance of the desalinator was improved by increasing solar radiation, ambient air temperature, initial water temperature in the tray and wind speed. In addition, performance is associated with the thermal conductivity of the materials used in the desalinator, a high productivity rate can be achieved using thermal absorbent materials, such as the use of fins, nano fluids and sponges integrated in the desalinator. Therefore, it was possible to conclude that the climatic, operational and design parameters inherent to the solar desalinator, are determining factors to improve the productivity of desalinated water.